Perlocutionary acts in Diera Nathania’s YouTube channel - Hidayat, Salsabila Nadhifah Nur; Fitriana, Ita; Firmansyah, Dian Bayu (Japanese Research on Linguistics, Literature, and Culture, 2023)
This study aims to analyze the effect of perlocutionary acts used when communicating in vlogs. This is qualitative descriptive research. The theory used to analyze the data in this study is Leech's theory of perlocutionary verbs. The data source in this study is Diera Nathania's YouTube channel, and the data is perlocutionary acts contained in the vlog. The data in this study were analyzed using documentation techniques and note-taking. The results showed that there were 2 utterances containing the perlocutionary verb get hearer to think about, 13 data to bring hearer to learn that, get hearer to do 4 data, 2 data distract, 1 data persuade, 1 data encourage, 1 data relieve tension, 2 data inspire, 1 data embarrass, 1 data frighten. Speeches that contain perlocutionary verbs teach the hearer what is most widely used to make YouTube viewers know something.